Developing and supporting multiculturalism and leadership development : International perspectives on humanizing higher education - Sengupta, Enakshi; Blessinger, Patrick; Makhanya, Mandla S. (Innovations in higher education teaching and learning, 2020)
The modern notion of humanism centres on the core qualities in all humans: agency, dignity, and development; primarily concerned with addressing contemporary human needs, concerns and problems. This book has an interdisciplinary focus on the development of human capacity at all levels, with the view that higher education is well suited for all.